Generalized Lomb–Scargle analysis of $$\mathrm {^{90}Sr/^{90}Y}$$ 90Sr/90Y decay rate measurements from the Physikalisch–Technische Bundesanstalt - P. Tejas; Shantanu Desai (European Physical Journal C: Particles and Fields, 2018)
Abstract We apply the generalized Lomb–Scargle (LS) periodogram to independently confirm the claim by Sturrock et al. (Astropart Phys 84:8. https://doi.org/10.1016/j.astropartphys.2016.07.005, 2016) of an oscillation at a frequency of 11/year in the decay rates of $$\mathrm {^{90}Sr/^{90}Y}$$ 90Sr/90Y from measurements at the Physikalisch Technische Bundesanstalt (PTB), which however has been disputed by Kossert and Nahle (Astropart Phys 69:18. https://doi.org/10.1016/j.astropartphys.2015.03.003, 2015). For this analysis, we made two different ansatze for the errors. For each peak in the LS periodogram, we evaluate the statistical significance using non-parametric bootstrap resampling. We find using both of these error models evidence for  11/year periodicity in the $$\mathrm {^{90}Sr/^{90}Y}$$ 90Sr/90Y data for two of the three samples, but at a lower significance than claimed by Sturrock et al. [1].